Предмет: Химия,
автор: glowpriority
Цепочка реакций:
Fe = FeSO4 = (FeOH)2SO4 = Fe(OH)2 = Fe(OH)3 = Fe(H2PO4)3
Ответы
Автор ответа:
0
Ответ:
Объяснение:
Fe - FeSO4 - (FeOH)2SO4 - Fe(OH)2 - Fe(OH)3 - Fe(H2PO4)3
Fe + H2SO4(разб.) = FeSO4 + H2↑
2FeSO4 + 2H2O = (FeOH)2SO4 + H2SO4
(FeOH)2SO4 + 2NaOH = 2Fe(OH)2 + Na2SO4
4 Fe(OH)2 + O2 + 2H2O = 4Fe(OH)3
Fe(OH)3 + 3H3PO4 = Fe(H2PO4)3 + 3H2O
Похожие вопросы
Предмет: Математика,
автор: voiceacting33
Предмет: Английский язык,
автор: Аноним
Предмет: Геометрия,
автор: darahezer54
Предмет: Русский язык,
автор: 89268577704